Integrating Critical Thinking Into Agricultural Communications Curricula - Ricky Telg; Tracy Irani (Journal of Applied Communications, 2005)
Agricultural communications instructors were provided with summary findings from a previous study on agricultural communications undergraduate majors’ level of critical thinking skills and were asked to respond to the findings by determining reasons why students’ skills were low, identifying ways to enhance critical thinking in courses, and stating the benefits for students to have strong critical thinking skills. Respondents identified these factors that contribute to agricultural communications students’ lack of critical thinking skills: an inability to read critically or to read well, a lack of analytical skills, and a lack of curiosity. The instructors identified four major areas to better utilize critical thinking in their courses: using real-world projects and situations, emphasizing research, demanding more and richer writing assignments, and exposing students to differing viewpoints. The benefits to students for having strong critical thinking skills include becoming conscientious consumers of information, mature leaders, and better employees. Recommendations for implementing critical thinking into agricultural communications curricula include providing opportunities for real-world, practical projects; incorporating case studies into courses; incorporating varying viewpoints—not just a proagriculture attitude; and emphasizing analysis of information—not just finding information.